The Role of Ureteroscopy in the Treatment of Renal Transplantation Complications - Basiri, Abbas; Simforoosh, Nasser; Nikoobakht, Mohammad Reza; Hosseini Moghadam, Mohammad Mehdi (Urology Journal, 2009)
Purpose: To determine the feasibility, safety, and efficacy of diagnostic and therapeutic ureteroscopy in renal allograft ureters. Materials and methods: We reviewed 1560 consecutive renal allografts have been preformed between June 1989 and February 2002.Twenty-eight patients (1.8%) had indication for endoscopic procedure on allograft ureter. Six patients had obstructive ureteral calculi with a history of failed ESWL, 3 had suspected ureteral stricture, 9 had upward migrated ureteral stents and 10 had ureteral stricture at ureteroneocystostomy site. Ureters were anastomosed to bladder using Leadbetter- Politano and Lich-GreGoire methods in 6 and 22 cases, respectively. Ureteroscopies were performed with semi rigid 9.8F wolf ureteroscope. Results: Identifying and introducing the ureteral orifice was successful in 19 (68%) cases. If we exclude 10 patients with ureteral stricture, ureteroscopy was successful in 13 out of 18 (72%). Four ureteral calculi (67%) were removed with ureteroscope.Seven out of nine migrated stents (78%) were retrieved. Four patients with ureteral stricture at ureteroneocystostomy site (40%) had successful ureteral dilatation and double J ureteral catheters were also inserted. Diagnostic ureteroscopy was successful in all cases. Two complications including one urinary leakage and one symptomatic urinary tract infection occurred that were managed conservatively. Conclusion: Ureteral endoscopy was safe and effective method for management of urological complications after RT (renal transplantation). This procedure can be considered as the first choice compared with percutaneous and antegrade modalities.